Numerical simulations of active flow control with synthetic jets in a Darrieus turbine (2017)
This study presents two-dimensional numerical simulations of the flow around a cross-flow vertical-axis water turbine (straight-bladed Darrieus type) using active flow control by means of synthetic jets. The performance of the turbine is quantitatively analyzed from the hydrodynamic coefficients (torque coefficient, power coefficient, tangential force coefficient, normal force coefficient, lift coefficient and drag coefficient) and qualitatively by the flow behavior (vorticity field). Numerical simulations of the turbine were carried out using a time-accurate Reynolds-averaged Navier-Stokes (RANS) in ANSYS FLUENT with the shear stress transport turbulence model. A transient rotor-stator model with a sliding mesh technique was used to capture the changes in the flow field at each time step. Numerical results show that the use of synthetic jets over the extrados and intrados of the airfoil increases the net torque and power output of the turbine. Besides, this increment in the net power generated by the turbine is higher than the power consumed by the synthetic jets. Therefore, it is demonstrated that the global efficiency of the turbine increases by means of this active flow control technique. Several flow phenomena such as vortex shedding and their interference with the blades were also studied and analyzed